Transport and global warming : what is the potential for carbon reduction in Scotland? - Hickman, R; McCartney, P; Banister, D (Transport Studies Unit, University of Oxford, 2007)
Transport is a major user of carbon-based fuels, and achievement of the targets set at the Kyoto Protocol and elsewhere mean that the EU and national governments must reduce CO2 emissions in all sectors, including transport. This will be a difficult task and will require action on many fronts. This paper reports on two recently completed studies considering these issues – for the UK Department for Transport and the Scottish Executive. The core analysis considers the options available to meet a 60% CO2 reduction target by 2030 in the transport sector at the UK level and, using an innovative backcasting study approach, develops a business as usual (BAU) baseline for transport emissions, and alternative scenarios to 2030. Different policy measures are assessed and assembled into mutually supporting combinations. These are grouped into policy packages to establish whether the challenging 60% CO2 reduction target can be reached and when the key actions need to be taken. The distinct role that can be played in Scotland is also reviewed, considering the likely policy options available, using “new” policy measures or a ”more intensive” application of existing policy measures. Although 2030 seems a long way ahead, action must be taken now in Scotland if the targets for CO2 reduction are to be met. The opportunity is there to develop a niche as a market leader in carbon efficient transport. Combining this with behavioural change, aimed at holding car-based travel at or near to present levels, will help Scotland move towards even the more stringent carbon reduction targets. A major transformation in the way transport and urban planning is carried out is however required. As transport, urban planners and the public we need to think very differently in tackling the new environmental imperative.